SHARIA ACCOUNTING PRACTICES AND FINANCIAL ACCOUNTABILITY IN ISLAMIC MICROFINANCE INSTITUTIONS: A CASE STUDY OF BAITUL MAAL WA TAMWIL IN MEDAN CITY - Adawiyah, Rabiatul; Nasution, Yenni Samri Juliati; Nasution, Juliana (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines the role of sharia accounting practices in strengthening transparency and accountability of financial reporting in Islamic microfinance institutions, with a particular focus on Baitul Maal wa Tamwil (BMT) in Medan City. As community-based financial institutions, BMTs play a strategic role in supporting socio-economic empowerment while adhering to Islamic principles of justice, honesty, and trustworthiness. Sharia accounting is therefore not only a technical reporting mechanism but also an ethical framework that shapes responsible financial governance within Islamic communities. This research adopts a qualitative case study approach. Data were collected through in-depth interviews with BMT managers, internal auditors, sharia supervisory board members, and staff, complemented by document analysis of financial reports and relevant regulatory guidelines. The findings reveal that the implementation of sharia accounting contributes significantly to improving transparency through detailed transaction recording, clear disclosure of sharia-based contracts, and separation of social and commercial funds. Accountability is strengthened through internal supervision, sharia compliance mechanisms, and adherence to PSAK Syariah and AAOIFI standards. Nevertheless, the study also identifies challenges, particularly limited human resource capacity and the lack of integrated accounting systems. This study contributes to the discourse on Islamic community development by demonstrating how sharia accounting can support accountable and transparent financial governance in Islamic microfinance institutions.